An inter-subunit protein-peptide interface that stabilizes the specific activity and oligomerization of the AAA+ chaperone Reptin - Coufalova, Dominika (2020)
Reptin is a member of the AAA+ superfamily whose members can exist in equilibrium between monomeric apo forms and ligand bound hexamers. Inter-subunit protein-protein interfaces that stabilize Reptin in its oligomeric state are not well-defined. A self-peptide binding assay identified a protein-peptide interface mapping to an inter-subunit “rim” of the hexamer bridged by Tyrosine-340. A Y340A mutation reduced ADP-dependent oligomer formation using a gel filtration assay, suggesting that Y340 forms a dominant oligomer stabilizing side chain. The monomeric ReptinY340A mutant protein exhibited increased activity to its partner protein AGR2 in an ELISA assay, further suggesting that hexamer formation can preclude certain protein interactions. Hydrogen-deuterium exchange mass spectrometry (HDX-MS) demonstrated that the Y340A mutation attenuated deuterium suppression of Reptin in this motif in the presence of ligand. By contrast, the tyrosine motif of Reptin interacts with a shallower pocket in the hetero-oligomeric structure containing Pontin and HDX-MS revealed no obvious role of the Y340 side chain in stabilizing the Reptin-Pontin oligomer. Molecular dynamic simulations (MDS) rationalized how the Y340A mutation impacts upon a normally stabilizing inter-subunit amino acid contact. MDS also revealed how the D299N mutation can, by contrast, remove oligomer de-stabilizing contacts. These data suggest that the Reptin interactome can be regulated by a ligand dependent equilibrium between monomeric and hexameric forms through a hydrophobic inter-subunit protein-protein interaction motif bridged by Tyrosine-340. Significance: Discovering dynamic protein-protein interactions is a fundamental aim of research in the life sciences. An emerging view of protein-protein interactions in higher eukaryotes is that they are driven by small linear polypeptide sequences; the linear motif. We report on the use of linear-peptide motif screens to discover a relatively high affinity peptide-protein interaction for the AAA+ and pro-oncogenic protein Reptin. This peptide interaction site was shown to form a ‘hot-spot’ protein-protein interaction site, and validated to be important for ligand-induced oligomerization of the Reptin protein. These biochemical data provide a foundation to understand how single point mutations in Reptin can impact on its oligomerization and protein-protein interaction landscape.